Instrument-Assisted Soft Tissue Mobilisation and Cryokinetics in Frozen Shoulder: A Critical Narrative Review of Comparative Effectiveness, Mechanistic Plausibility and Evidential Gaps - Nishi Lodha; Shilpa Ameta (Asian Journal of Medicine and Health, 2026)
Frozen shoulder is a painful and mobility-limiting condition of the glenohumeral joint whose fibrotic, inflammatory and neuro-immune substrate has been characterised in increasing detail over the past decade. Rehabilitation practice has nevertheless diversified faster than the supporting evidence, and two mechanically dissimilar adjuncts have entered routine use: instrument-assisted soft tissue mobilisation, in which rigid ergonomic tools deliver controlled shear and compressive loads to periarticular soft tissue, and cryokinetics, in which localised cooling to numbness is followed immediately by graded active exercise. Clinicians are increasingly asked to choose between them, yet the comparative basis for that choice has not been examined critically. This review defines the conceptual boundaries of both interventions, appraises the direct and indirect evidence for each in frozen shoulder and adjacent shoulder disorders, and evaluates whether the two literatures can support a defensible comparative conclusion. Searching of open scholarly databases and citation tracking identified one randomised trial of instrument-assisted soft tissue mobilisation conducted specifically in adhesive capsulitis, several shoulder-region trials in other diagnoses, and three recent meta-analyses of mixed musculoskeletal populations. No controlled trial of cryokinetics in frozen shoulder was identified, and the cryokinetics literature rests largely on ankle and tendon models, a small number of shoulder tendinopathy trials of limited methodological quality, and physiological studies of cooling. The two evidence bases therefore differ not merely in magnitude but in maturity, outcome selection and risk of bias, and no head-to-head trial exists. Claims of superiority for either modality in frozen shoulder are consequently unsupported. Reported benefits are modest, short-term and vulnerable to non-specific effects, and cooling before exercise raises unresolved questions about proprioceptive and force-generating impairment. Priorities include a sham-controlled dose-defined trial programme, standardised force reporting, and stage-stratified designs anchored to clinically meaningful thresholds.